Rules-Based Fiscal Policy in Emerging Markets : Background, Analysis, and Prospects - Kopits, George (International Monetary Fund, 2004)
Inspired by the experience of some advanced economies and to enhance creditworthiness, recently a number of emerging market economies adopted rules limiting government deficits, expenditures, or indebtedness. This volume consists of 15 chapters-written by distinguished policy analysts and academics-that focus on the potential usefulness of fiscal rules for these economies, and highlight their brief experience with rules.